Sustainability of the German Pension Scheme: Employment at Higher Ages and Incentives for Delayed Retirement - Lewicki, Maria Patricia (KIT Scientific Publishing, 2014)
The aging society and threatening old-age poverty are two major political topics in Germany for the next decades. Many modern employment biographies consist of atypical employment and discontinuities; both negatively impact the pension entitlements of the individuals. This work develops an inninnovative approach that offers flexibility to absorb demographic changes as well as labor market developments, without threatening the financial stability of the public pension scheme.